Promoting a Better Image through Culture: The Case of Turkey’s Cultural Diplomacy towards Indonesia - Rifkha Aulia Fazrianti Zaelani; Ahmad Sahide (Universitas Muhammadiyah Yogyakarta, 2021)
This study attempts to reveal cultural diplomacy, which Turkey implements towards Indonesia. The ‘golden period’ of Turkey is from 2007 until 2013. After that, the public diplomacy of Turkey was not effective as before, and it was fallen dramatically. The country’s instability caused by the political turmoil within the country also influences the growth of international isolation. With these based on the problem that influences its image, Turkey needs to prove a different and better image to promote itself abroad. Public perceptions can be shaped and controlled by doing cultural diplomacy that acts as soft power. Having one thing in common as a country with a Muslim population as the majority, Turkey has a special place in the hearts of the Indonesian people. Based on the theory of cultural diplomacy by Milton C. Cummings, the authors drew two arguments. First, Turkey’s Cultural diplomacy towards Indonesia is done not only by state actors (officially by the government) but also by non-state actors such as individuals and companies. Second, cultural diplomacy carried out by Turkey towards Indonesia is through all aspects of the needs of the Indonesian people, such as films, fashion, news, music, food, and education.